2021
DOI: 10.55705/cmbr.2021.361362.1063
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective observational study to assess the cirrhosis risk in alcoholic patients

Abstract: Cirrhosis is a late-stage liver disease in which/ advanced stage of scaring and conditions, such as hepatitis and chronic alcoholism. This disease is a condition in which your liver is scarred and permanently damaged. Scar tissue replaces healthy liver tissue and prevents your liver from working normally. Irreversible change in the normal liver tissue results in the degeneration of functioning liver cells and their replacement with fibrous connective tissue. In the present study, the risk assessment in alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Lymphocyte populations are exceptionally sensitive to apoptosis, and the amount of B cells and T cells are distinctly reduced after sepsis onset (19,20). It would cause increased mortality if the cell numbers of leukocytosis or lymphopenia can not be normalized during the stages (20)(21)(22)(23)(24)(25)(26)(27)(28). This study suggested that the stress induced by sepsis mainly influences the macrophage function related to T cell activation and differentiation, and lymphocyte differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…Lymphocyte populations are exceptionally sensitive to apoptosis, and the amount of B cells and T cells are distinctly reduced after sepsis onset (19,20). It would cause increased mortality if the cell numbers of leukocytosis or lymphopenia can not be normalized during the stages (20)(21)(22)(23)(24)(25)(26)(27)(28). This study suggested that the stress induced by sepsis mainly influences the macrophage function related to T cell activation and differentiation, and lymphocyte differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…Given the role of Res as an inhibitor of oxidative stress, inflammation, and hyperhomocysteinemia (23)(24)(25)(26)(27)(28)(29)(30), it may also serve to counteract the negative effects of hyperglycemia as observed in the present study, thereby reversing the impaired GC steroidogenesis observed following high-glucose treatment. However, further research will be essential to clarify the molecular mechanisms governing these Res-mediated improvements in GC function in order to better explore the potential clinical utility of this natural compound.…”
Section: Res Alters Gc Apoptosis-related Gene Expressionmentioning
confidence: 85%
“…In addition, it has been reported that lncRNAs could affect tumors by regulating autophagy. Qiong Wu et al (35) proposed that autophagy promoted GC cell survival, migration, invasion and EMT, and their study revealed that Ln-cRNA SnHG1 1 activated the Wnt/ β catenin pathway and aggravated GC progression via oncogenic autophagy (35)(36)(37)(38)(39)(40)(41)(42). Epithelial-mesenchymal transition (EMT) plays a prominent role in SCC progression, and it is closely related to the proliferation and migration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%